Pengaruh Kompetensi Sumber Daya Manusia, Kedisplinan Kerja, Motivasi Kerja Dan Insentif Terhadap Kinerja Pegawai Pada Puskesmas Suka Makmur Desa Tebing Linggahara Baru Kecamatan Bilah Barat - Tanjung, Halimah (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the competence of Human Resources, work discipline, work motivation and incentives to the performance of employees at Puskesmas Suka Makmur Tebing Linggahara Baru village Barat Barat District. This Type Of Research Is Associative Research. The data collection in this study was conducted through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 30 respondents, while the population used in this study were employees at Puskesmas Suka Makmur Tebing Linggahara Baru village, Barat Barat District. The results of this study showed that partially (t test) known that the competence of Human Resources positively and significantly affect the performance of employees at the Health Center Suka Makmur Tebing Linggahara Baru village Barat district with a value of thitung (5.387) > ttable 1.710) and the level of significance 0.000 < 0.05. Work discipline significantly positive effect on the performance of employees at the Health Center Suka Makmur Tebing Linggahara Baru village Barat district with the value of thitung is (3.831) > ttable (1.710) and the level of significance 0.001< 0.05. Work motivation significant positive effect on the performance of employees at the Health Center Suka Makmur Tebing Linggahara Baru village Barat district with the value of thitung is (4.804) > ttable (1.710) and the level of significance 0.000< 0.05. Then the incentive significantly positive effect on the performance of employees at the Health Center Suka Makmur Tebing Linggahara Baru village Barat district with the value of thitung is (5.828) > ttable (1.710) and the level of significance 0.000< 0.05. In the simultaneous testing (test F) known that the competence of Human Resources, work discipline, work motivation and incentives positive and significant effect on the work performance of employees at the Health Center Suka Makmur Tebing Linggahara Baru village Barat Barat with the results showed that the value of Fhitung is (49.076) > Ftable (2.76) and the level of significance 0.00 < 0.05. Through testing the coefficient of determination (Adjusted R Square) of 0.871 means 87.1% of the factors of performance in Puskesmas Suka Makmur Tebing Linggahara Baru village Barat district can be explained by the competence of Human Resources, work discipline, work motivation and incentives while the remaining 12.9% can be explained by other factors that are not studied in this study.